Impact of HPV E5 on viral life cycle via EGFR signaling. (February 2020) - Ilahi, Naureen Ehsan; Bhatti, Attya
Abstract: Oncoprotein E5 is gaining popularity with time as the third transforming protein of Human Papillomavirus (HPV). Extensive proliferation is the distinguished feature of developing cancers, and E5 is able to stimulate keratinocytes proliferation via upregulation of EGFR signaling pathway. Thus E5 is thought to indirectly contribute to the completion of the viral life-cycle by generating the adequate cellular environment. By amplifying EGFR signaling E5 delays differentiation and allows hyperproliferation of keratinocytes which otherwise would have followed a normal differentiation pathway. Thus exploring the mechanisms by which HPV E5 regulates signaling by EGFR receptors in detail suggest new ways of inhibiting HPV-mediated disease progression. Highlights: HPV E5 causes upregulation of EGFR signaling pathway. HPV E5 contributes to the completion of the viral life-cycle by generating the adequate cellular environment. E5 delays differentiation and allows hyperproliferation of keratinocytes.